2014
DOI: 10.1016/j.joen.2014.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Conventional and New-generation Nickel-Titanium Files in Regard to Their Physical Properties

Abstract: Introduction: The aim of this study was to investigate the surface and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 29 publications
(22 reference statements)
2
18
0
Order By: Relevance
“…In the literature, it was reported that the thermal treatment to the NiTi alloy increased flexibility by changing the composition of phases [14]. In this study, the EM of K3 was significantly higher than that of K3XF and K3H.…”
Section: Discussionmentioning
confidence: 54%
“…In the literature, it was reported that the thermal treatment to the NiTi alloy increased flexibility by changing the composition of phases [14]. In this study, the EM of K3 was significantly higher than that of K3XF and K3H.…”
Section: Discussionmentioning
confidence: 54%
“…, Tsujimoto et al . ). NiTi rotary instruments have superior flexibility, and their superelasticity decreases the restoring forces, thus allowing enhanced canal shaping and decreased transportation (Gergi et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Tsujimoto et al . ). Flexibility of NiTi rotary instruments is an important property as it reduces the iatrogenic errors that cause canal transportation and improves the root canal preparation (Lopes et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ProFile Vortex™ product is an M‐Wire file (Gao, Shotton, Wilkinson, Phillips, & Johnson, ), and served as the control. The subsequently marketed ProFile Vortex Blue™ product is an M‐Wire file in which the manufacturer performs a special heat treatment that yields a blue colour from the titanium oxide surface film (Plotino, Grande, Cotti, Testarelli, & Gambarini, ; Tsujimoto et al, ). The ProTaper Gold™ product is also a subsequently marketed M‐Wire file, but subjected to different metallurgical processing (Hieawy, Haapasalo, Zhou, Wang, & Shen, ; Uygun et al, ).…”
Section: Methodsmentioning
confidence: 99%